Financial and competitive implications of the European Green Seal: Perceptions of retail managers - Claudia Gabriela Baicu; Olimpia State; Daniel Adrian Gârdan; Iuliana Petronela Gârdan; Iulia Ruxandra Ticău (Amfiteatru Economic Journal, 2022)
Tackling climate change is one of the highest challenges which the world economy is currently facing. The European Green Deal, adopted in 2019, sets the European roadmap towards a net-zero greenhouse gas emissions economy. The food system is heavily responsible for greenhouse gas emissions and environmental degradation. Against this backdrop, the aim of the paper is to assess the way retail managers perceive the financial and competitive implications of the Green Deal in the activity of their companies. To achieve this goal, we have conducted qualitative research in the form of in-depth interviews in a sample of managers responsible for sustainability, quality or corporate social responsibility of important food retail companies in the Romanian market. The results of the research revealed different opinions and perceptions, but which converge to emphasize the importance of applying the principles underlying the Green Pact to gain competitive advantage and optimize costs, particularly, by developing solutions to reduce carbon emissions, use clean energy, reduce food waste and educate consumers towards sustainable consumption.
Keywords: L10; L25; L81; M10; O13; P18; Q01; 330; competition; European Green Deal; financial performance; food system; greenhouse gas emissions; retail